2021
DOI: 10.3390/vaccines9101184
|View full text |Cite
|
Sign up to set email alerts
|

The Immunology of Hepatocellular Carcinoma

Abstract: Liver cancer is the third leading cause of cancer death worldwide. Hepatocellular carcinoma (HCC) is the most common primary malignant tumor of the liver. Liver resection or transplantation offer the only potentially curative options for HCC; however, many patients are not candidates for surgical resection, either due to presentation at advanced stages or poor liver function and portal hypertension. Liver transplantation is also limited to patients with certain characteristics, such as those that meet the Mila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 101 publications
0
37
0
Order By: Relevance
“…However, the persistence of inflammation, sustained cell death, compensatory proliferation, activation of nonparenchymal cells, and an altered immune response can promote liver fibrosis and, in turn, lead to tumorigenesis [ 6 – 8 ]. Along with the occurrence of tumors, inflammatory signals, cellular stress, epigenetic modifications [ 9 ], mitochondrial stress signaling [ 10 ], and the immune system may change [ 11 ], thus posing significant challenges to the treatment and prognosis evaluation of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the persistence of inflammation, sustained cell death, compensatory proliferation, activation of nonparenchymal cells, and an altered immune response can promote liver fibrosis and, in turn, lead to tumorigenesis [ 6 – 8 ]. Along with the occurrence of tumors, inflammatory signals, cellular stress, epigenetic modifications [ 9 ], mitochondrial stress signaling [ 10 ], and the immune system may change [ 11 ], thus posing significant challenges to the treatment and prognosis evaluation of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, GO and KEGG analysis also revealed that C1QBP was highly associated with the ribosome-related process ( Figure S5 ). Considering the importance of immune cell infiltration in HCC progression 29 , we evaluated the correlation between C1QBP expression and immune cell infiltration which was score by multiple algorithms. However, no difference was observed in HCC patents stratified by C1QBP expression (Figure 8 A and 8 B) and there were only weak to no correlations between C1QBP expression and the infiltration of immune cells or known immune genes ( Figure S6 and Figure S7 ), suggesting that immune filtration may not be involved in the roles of C1QBP during HCC progression, at least based on the data from this bioinformatic quantification.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, we found that tumor suppressors were negatively correlated with the infiltration of pDCs, DCs, and cytotoxic cells, and the tumor promoters METTL3, VIRMA, and CBLL1 were positively correlated with Tcm and Th2 cell infiltration. Infiltration of DCs, Tcm and their derived cytotoxic T cells, along with Th2 cells, are generally considered to be protective factors for HCC ( Foerster et al, 2018 ; Lawal et al, 2021 ), which may be related to changes in the balance between DC subsets or T effector cells and regulatory T cells in tumors ( Lawal et al, 2021 ; Gao et al, 2007 ), suggesting that stratification of immune cell infiltration is the key to achieving effective treatments. Therefore, the interplay between the m 6 A writer complex and tumor microenvironment may be an important mechanism for the tumorigenesis and progression of HCC.…”
Section: Discussionmentioning
confidence: 99%